(untitled) (UNED Research Journal, 2015)
Tourism is an economic, social and cultural activity that exerts positive and negative influences on communities and ecosystems where it is implemented. Tourism is occurring in the Talamanca valley communities of Yorkín, Bambú and Shiroles (Costa Rica), where there is developing infrastructure and high tourist demand. Our aim was to analyze the environmental and socio- cultural influence of tourist lodges and homes in Talamanca Bribri territory. We visited ten communities in Bratsi and Telire, six with lodges and four without lodges. We interviewed those responsible for the tourist lodges and heads of households in communities with or without lodges. A conical type of construction dominates the tourist lodges, while wooden houses on stilts dominate communities without tourism. In communities with tourist lodges, there is significant, predominant use of non-traditional raw materials in the construction of stilts, walls and doors. In geographically-isolated communities traditional materials dominate, compared to the use of non-traditional materials in communities with greater connectivity. In communities with lodges, the breed- ing of domestic animals for meat consumption is a stronger tradition. In geographically-isolated communities, the native language and the kinship system is preserved. In the territory 21 clans according to the matrilineal kinship system were identified. There are no differences in the perception of the impact of tourism on communities. In communities with lodges or without them, the same socio-cultural practices are mentioned.